Desenvolvimento e avaliação de um protótipo para mensurar o espaçamento longitudinal entre sementes - Zart, Bruno Christiano Correa Ruiz (2019)
The objective was to develop and evaluate an automated system, in prototype form, to measure the longitudinal spacing in the distribution of corn and soybean seeds deposited on a test bench at different speed conditions.This was carried out in the Laboratório de Pesquisa e Desenvolvimento de Máquinas Agrícolas (LASERG), belonging to Universidade Federal de Santa Maria (UFSM). The prototype´s development was based on the design methodology, containing conceptual design, preliminary design and detailed design. For the evaluation, two experiments (one for corn seeds and one for soybean seeds) were carried out in a completely randomized design with 8 treatment combinations in a 4x2 factorial scheme. These were composed by the interaction of the factors forward speed (1.11, 1.67, 2.22 and 2.78 m s-1) and reading method (visual and prototype). The analyzed variables were seed spacing, percentage of seed detection, as well as absolute and relative spacing differences in relation to the two methods. After the data acquisition, they were submitted to the statistical analysis of variance and verified the significance of the factors through the F test, in addition, regression analyzes were performed. For the seed spacing variable, there was no significant interaction between the factor speed and the factor reading method, as well as the fator method did not present significant influence on the same variable for both the corn seed and the soybean seed. However, the factor speed had significant influence on the variable spacing for both types of seed. The prototype obtained a percentage of detection of corn seeds, moderately higher when compared to soybean seeds. The prototype proved to be an efficient method for measuring the spacing between corn and soybean seeds.